2017
DOI: 10.1007/s40653-017-0163-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying and Internalizing Difficulties among Indigenous Adolescents in Canada: Beyond the Effect of Traditional Bullying

Abstract: Most research on bullying and cyberbullying has focused on dominant populations. In particular, inquiries into Indigenous adolescents' involvement in bullying and cyberbullying are scarce. The present study examines the relationship between bullying and cyberbullying involvement and self-reported depression, anxiety, and stress among a sample of 170 Indigenous adolescents (54% female; M age = 15.2 years). Controlling for age and gender, the results of a series of hierarchical multiple regression models indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
5
22
0
Order By: Relevance
“…Second, by relying on a static, three-/four-pronged definition of bullying, which originated within a western social, cultural, and academic context, research has tended to be blind to important markers of social and cultural difference (Bodkin-Andrews, O'Rourke, Dillon, Craven, & Yeung, 2012;Coffin, Larson, & Cross, 2010). On the one hand, despite indications that minority populations experience higher rates of cyberbullying (Llorent, Ortega-Ruiz, & Zych, 2016), research has tended to be demographically limited (Broll et al, 2018;Mobin et al, 2017), focusing mainly on white, urban populations, differentiating research participants only by age and (binary) gender (Brownlee et al, 2014;Kowalski et al, 2014;Mobin et al, 2017). Consequently, it has largely overlooked non-majority populations, including ethnic, cultural, differently-abled, sexual, gender, and religious minorities.…”
Section: Difference Blindness and Cultural Imperialismmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, by relying on a static, three-/four-pronged definition of bullying, which originated within a western social, cultural, and academic context, research has tended to be blind to important markers of social and cultural difference (Bodkin-Andrews, O'Rourke, Dillon, Craven, & Yeung, 2012;Coffin, Larson, & Cross, 2010). On the one hand, despite indications that minority populations experience higher rates of cyberbullying (Llorent, Ortega-Ruiz, & Zych, 2016), research has tended to be demographically limited (Broll et al, 2018;Mobin et al, 2017), focusing mainly on white, urban populations, differentiating research participants only by age and (binary) gender (Brownlee et al, 2014;Kowalski et al, 2014;Mobin et al, 2017). Consequently, it has largely overlooked non-majority populations, including ethnic, cultural, differently-abled, sexual, gender, and religious minorities.…”
Section: Difference Blindness and Cultural Imperialismmentioning
confidence: 99%
“…Despite this, research to date has largely overlooked Indigenous people's experiences of cyberbullying. The small body of available research specifically on Indigenous cyberbullyingin Canada (Broll, Dunlop, & Crooks, 2018;Brownlee et al, 2014;Mobin, Feng, & Neudorf, 2017), the US (Samulski, 2014), and Australia (Carlson & Frazer, 2018a;Radoll, 2012;Vaarzon-Morel, 2014)has yielded important insights, particularly in demonstrating that we cannot assume cyberbullying occurs at the same rate, for the same reasons, and with the same impacts, as for non-Indigenous peoples.…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns were found for friendship quality, however, friendship quality only attenuated the link between cyberbullying victimization and feelings of distress. Focusing on yet another understudied group of youth, Broll et al (2018) study the association between traditional bullying and cyberbullying involvement and depression, anxiety, and stress among Canadian indigenous adolescents. After accounting for age and gender, cyberbullying victimization was associated with greater reports of anxiety and stress while including traditional bullying victimization in the analysis, suggesting a unique contribution of experiencing cyberbullying.…”
Section: What We Learn From the Contributions Of The Special Issuementioning
confidence: 99%
“…Kowalski et al (2016) found that being cyberbullied was especially linked to low self-esteem and greater depression among college students with a disability. Moreover, research in this special issue highlights how LGBTQ youth who are cyberbullied report a number of psychological, emotional, behavioral and academic problems (Abreu and Kenny 2018), and that Indigenous adolescents in Canada who are cyberbullied report higher levels of anxiety and stress, over and above the impact of school bullying (Broll et al 2018). Thus, given our growing understanding of the ways in which youth are impacted by cyberbullying and given that this may be further complicated given the challenges they face as members of marginalized groups, it is important for future work to test and identify factors that may protect youth from the pain of being victimized online.…”
Section: Identification Of Protective Factorsmentioning
confidence: 99%
“…For example, the victims may experience depression, social anxiety, low self-esteem, loneliness, sadness, fear, etc. (Broll, Dunlop, & Crooks, 2018;Wong & Mcbride, 2018;Gahagan, Vaterlaus, & Frost, 2016;Bauman, Toomey, & Walker, 2013;Balakrishnan, 2015). The deterioration of these psychological problems may lead to a series of negative consequences including suicide, sleep disorders, substance abuse, decreased academic performance, and tensions among family members (Wong & Mcbride, 2018;Bauman, Toomey, & Walker, 2013;Anderson, Bresnahan, & Musatics, 2014;Broll, Dunlop, & Crooks, 2018).…”
Section: Introductionmentioning
confidence: 99%